2021
DOI: 10.3389/fpubh.2021.657987
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Flavoring-Related Lung Disease in a Coffee Roasting and Packaging Facility Worker With Unique Lung Histopathology Compared With Previously Described Cases of Obliterative Bronchiolitis

Abstract: Occupational exposure to diacetyl, a butter flavor chemical, can result in obliterative bronchiolitis. Obliterative bronchiolitis is characterized by exertional dyspnea, fixed airflow obstruction, and histopathologic constrictive bronchiolitis, with bronchiolar wall fibrosis leading to luminal narrowing and obliteration. We describe a case of advanced lung disease with histopathology distinct from obliterative bronchiolitis in a 37-year-old male coffee worker following prolonged exposure to high levels of diac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
(40 reference statements)
2
9
0
Order By: Relevance
“…Ground coffee, flavored coffee, liquid flavorings, and off-gassing bins or packages were also identified as the highest sources of diacetyl and 2,3-pentanedione. Elevated task, instantaneous activity, and instantaneous source exposures associated with grinding and flavoring tasks are consistent with the work history of a coffee production worker diagnosed with obliterative bronchiolitis, who performed grinding and flavoring tasks for 7 years prior to diagnosis in the grinding area and flavoring room of one of the 17 coffee and roasting facilities described here ( 12 ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Ground coffee, flavored coffee, liquid flavorings, and off-gassing bins or packages were also identified as the highest sources of diacetyl and 2,3-pentanedione. Elevated task, instantaneous activity, and instantaneous source exposures associated with grinding and flavoring tasks are consistent with the work history of a coffee production worker diagnosed with obliterative bronchiolitis, who performed grinding and flavoring tasks for 7 years prior to diagnosis in the grinding area and flavoring room of one of the 17 coffee and roasting facilities described here ( 12 ).…”
Section: Discussionsupporting
confidence: 77%
“…Five cases of obliterative bronchiolitis observed among current and former coffee production workers were first described in 2013 and 2015 ( 21 , 22 ). Since then, two recent case reports have described additional cases of obliterative bronchiolitis in workers exposed to diacetyl and 2,3-pentanedione in coffee production ( 12 , 35 ) including a case of obliterative bronchiolitis observed in a current worker at one of the 17 coffee production facilities included in our study here ( 12 ). Observed cases of obliterative bronchiolitis among current and former workers in coffee production facilities along with measurements of elevated exposures to diacetyl and 2,3-pentanedione in the 17 facilities surveyed here ( 13 ) highlights a need to understand determinants of exposures to alpha-diketones in coffee production facilities such that exposure mitigation strategies can be designed and implemented accordingly.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies in flavoring workers have observed increasing symptoms and lung function abnormalities prior to the development of OB (25). Symptoms of chronic respiratory impairment and respiratory abnormalities, one case of OB identified in this workforce (9), and the observed associations with α-diketone exposures in this study may be indicative of early disease markers.…”
Section: Association Of α-Diketone Exposures With Lung Function Decre...supporting
confidence: 53%
“…Coffee production workers are exposed to complex mixtures of gases, dust, and vapors such as carbon monoxide, carbon dioxide, coffee dust, green-bean allergens, and α-diketones, including 2,3-butanedione (diacetyl-a commonly used synonym) and 2,3-pentanedione (acetyl propionyl), and other volatile organic compounds (VOCs), including acetoin (1)(2)(3)(4)(5)(6). Adverse respiratory health outcomes such as respiratory symptoms, pulmonary function abnormalities, asthma, and obliterative bronchiolitis (OB) can occur among exposed coffee production workers (7)(8)(9). OB is a rare, irreversible lung disease characterized by inflammation and bronchiolar wall fibrosis, leading to luminal narrowing of the small airways (i.e., bronchioles) and obliteration that obstructs airflow (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The α-diketone-related respiratory abnormalities occurred in both flavoring and non-flavoring workers, however in the flavoring workers all exposure metric means were numerically higher, the model coefficients were larger, and the associations were more consistent across both α-diketones. Additionally, Harvey et al ( 15 ) described a case of advanced lung disease in a coffee worker who had worked in the flavoring room and coffee grinding area of a coffee facility for a number of years. Although the biopsy findings were not typical of obliterative bronchiolitis, the authors noted that lung pathology may vary in flavoring-related lung disease.…”
Section: Introductionmentioning
confidence: 99%